Otteluiden ja 16 vuorokauden harjoitusjakson vaikutukset kuormittumis- ja palautumismuuttujiin tyttöjalkapalloilijoilla - Malmivuori, Janne (2025)
Malmivuori, J. 2025. Effects of Matches and a 16-Day Training Period on Load and Recovery Variables in Junior Female Football Players. Faculty of Sport and Health Sciences, University of Jyväskylä, Master’s thesis, 70 pp. The purpose of this study was to monitor the effects of match load and changes in overall load during a 16-day research period on the training status of junior female football players. Additionally, the study examined the relationships between changes in various training status indicators and overall load, as well as the interrelationships between the training status indicators. Total of 14 junior female football players (age: 16,7 ± 1,0 years; height: 167,6 ± 4,0 cm; weight: 59,4 ± 6,7 kg) participated in this study. The study period was divided into pre-MP (5 training sessions), MP- (4 training sessions + 4 matches) and post-MP (3 training sessions) phases. The participants’ external and internal loads were measured during all training sessions and matches throughout the study period using a wearable player monitoring system. CMJ height and submaximal running test heart rate variables (HR30s, HR60s, and HRR) were collected across 10 training sessions. Additionally, nocturnal HR and HRV (SDNN, lnRMSSD, lnHF, and lnLF) were monitored during each night of the study period. Saliva samples were collected from participants every morning during the study period. Salivary alpha-amylase activity, as well as salivary cortisol and DHEA-S concentrations were analyzed from the samples. Significant variation in the load of the participants was observed on days around the match days (MD-2 to MD+3) as well as between the different phases of the study period. Of the training status variables, significant fluctuations were found in the CMJ, HR30s, alpha-amylase and DHEA-S measures across the days surrounding the matches, while HRR, cortisol, nocturnal HR and HRV remained unchanged. When comparing the pre- and post-MP phases of the study, HR60s (173,5 ± 8,9 vs. 170,0 ± 8,8; p < 0,05), HR30s (175,0 ± 8,5 vs. 171,3 ± 8,2; p < 0,05) and salivary cortisol (19,0 ± 5,9 vs. 13,1 ± 5,1; p < 0,05) were found to decrease. However, significant associations were observed only between the changes in CMJ, lnRMSSD and lnLF and load variables throughout the study period (r = |0,572–0,775|; p < 0,05). Analysis of the relationships between training status measures revealed moderate to strong correlations between submaximal running test HR variables and nocturnal HR and HRV (r = |0,560–0,780|; p < 0,05). Match load and short-term fluctuations in overall load caused changes in the training status of junior female football players. However, the interpretation of these changes is not straightforward as significant changes were observed in only some of the measures. The HR and HRR measured during a submaximal running test, however, show potential as effective monitoring tools for tracking team sport athletes. Key words: football, load, recovery, monitoring